Complex network analysis of fine particulate matter (PM2.5): transport and clustering - N. Ying; W. Duan; Z. Zhao; J. Fan (Earth System Dynamics, 2022)
In this paper, complex network theory has been applied to reveal the transport patterns and cooperative regions of fine particulate matter (PM2.5) over China from 2015 to 2019. The results show that the degrees, weighted degrees, and edge lengths of PM2.5 cities follow power law distributions. We find that the cities in the Beijing–Tianjin–Hebei–Henan–Shandong (BTHHS) region have a strong ability to export PM2.5 pollution to other cities. By analyzing the transport routes, we show that a mass of links extends southward from the BTHHS to the Yangtze River Delta (YRD) regions with 1 or 2 d time lags. Hence, we conclude that earlier emission reduction in the BTHHS region and early warning measures in the YRD region will provide better air pollution mitigation in both regions. Moreover, significant links are concentrated in wintertime, suggesting the impact of the winter monsoon. In addition, all cities have been divided into nine clusters according to their spatial correlations. We suggest that the cities in the same clusters should be regarded as a whole to control the level of air pollution. This approach is able to characterize the transport and cluster for other air pollutants, such as ozone and NOx.